Sport psychology services to professional athletes: working through COVID-19 - Schinke, R.; Papaioannou, A.; Maher, C.; Parham, W. D.; Hvid Larsen, C.; Gordin, R.; Cotterill, S. (International Journal of Sport and Exercise Psychology, 2020)
Fandom around the world yearns for sports entertainment. Much of the discussions within the recent flurry of sport and exercise psychology writings have been focused on the challenging experiences of potential Olympians during an Olympic year. Indeed, the 2020 Olympics is an entertainment event like few others across sport levels.